Psychological characteristics of manifestation of internet addiction in teen-age - Meloyan, А. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
The article provides theoretical analysis and experimental study which reveal the psychological characteristics of manifestation of internet addiction in teen-age. Author mark some factors negatively influencing on psychological autonomy from internet space in adolescence.
Keywords: cyberspace; internet addiction; addictive behavior; self-esteem strategy; strong-willed potential